A review of reviews exploring patient and public involvement in population health research and development of tools containing best practice guidance - Soo Vinnicombe; Mayara S. Bianchim; Jane Noyes (BMC, 2023)
Abstract Introduction Patient and public involvement (PPI) is increasingly seen as something that is integral to research and of importance to research funders. There is general recognition that PPI is the right thing to do for both moral and practical reasons. The aim of this review of reviews is to examine how PPI can be done 'properly' by looking at the evidence that exists from published reviews and assessing it against the UK Standards for Public Involvement in Research, as well as examining the specific features of population health research that can make PPI more challenging. Methods A review of reviews and development of best practice guidance was carried out following the 5-stage Framework Synthesis method. Results In total 31 reviews were included. There is a lack of current research or clarity around Governance and Impact when findings are mapped against UK Standards for Public Involvement in Research. It was also clear that there is little knowledge around PPI with under-represented groups. There are gaps in knowledge about how to ensure key specific attributes of population health research are addressed for PPI team members - particularly around how to deal with complexity and the data-driven nature of the research. Four tools were produced for researchers and PPI members to further improve their PPI activity within population health research and health research more generally, including a framework of recommended actions to address PPI in population health research, and guidance on integrating PPI based on the UK Standards for Public Involvement in Research. Conclusions Facilitating PPI in population health research is challenging due to the nature of this type of research and there is far less evidence on how to do PPI well in this context. The tools can help researchers identify key aspects of PPI that can be integrated when designing PPI within projects. Findings also highlight specific areas where more research or discussion is needed.